INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) RESEARCH TRENDS IN MATHEMATICS LEARNING - Wahyuni, Astri; Kusumah, Yaya Sukjaya; Priatna Martadiputra, Bambang Avip; Purwasih, Ratni; Muhammad, Ilham; Zafrullah, Zafrullah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
The emergence of ICT in teaching and learning has contributed to improving the quality of education, because teaching and learning is ultimately an active and interesting process linked to real-world situations. ICT can be integrated into all subjects outside of physical education, including language, comprehension, math, science, and environmental science. This research examines trends and identifies publications concerning ICT in Mathematics Learning by analyzing the most prolific document sources, rankings of institutions or universities, prominent journals and articles, as well as keyword usage. Utilizing data from the Dimensions database, a total of 390 documents were gathered through the Publish or Perish (PoP) application, consolidated into a single RIS file, and analyzed using the VOSviewer application to generate network and overlay visualizations.The findings reveal an increasing trend in publications on ICT in Mathematics Learning over the past five years, with Indonesia leading in the number of documents (66), "Guangxi Normal University" as the top institution, "Journal of Physics: Conference Series" as the most prominent journal, and the article by Lo et al. (2018) as a key reference. The keyword "ICT" is not commonly associated with other variables such as case studies or stems, presenting a gap that offers opportunities for future research in this area.Penggunaan Teknologi Informasi dan Komunikasi (TIK) dalam pembelajaran telah berperan dalam meningkatkan kualitas pendidikan, menjadikan proses pembelajaran lebih aktif, menarik, dan relevan dengan situasi dunia nyata. TIK dapat diintegrasikan ke dalam berbagai mata pelajaran, seperti bahasa, pemahaman, matematika, sains, dan ilmu lingkungan, kecuali pendidikan jasmani. Penelitian ini mengeksplorasi tren dan mengidentifikasi publikasi terkait TIK dalam Pembelajaran Matematika melalui analisis jumlah dokumen terbanyak, peringkat institusi atau universitas, jurnal, dokumen, serta penggunaan kata kunci berdasarkan data dari basis data Dimensions. Dengan menggunakan analisis bibliometrik, 390 dokumen dikumpulkan melalui aplikasi Publish or Perish (PoP), dikompilasi ke dalam satu file RIS, dan dianalisis menggunakan aplikasi VOSviewer untuk menghasilkan visualisasi jaringan dan hamparan. Temuan menunjukkan adanya tren peningkatan publikasi tentang TIK dalam Pembelajaran Matematika selama lima tahun terakhir, dengan Indonesia memimpin dalam jumlah dokumen (66), “Guangxi Normal University” sebagai institusi teratas, “Journal of Physics: Conference Series” sebagai jurnal yang paling menonjol, dan artikel oleh Lo dkk. (2018) sebagai referensi utama. Kata kunci “TIK” tidak umum dikaitkan dengan variabel lain seperti studi kasus atau batang tubuh, menghadirkan celah yang menawarkan peluang untuk penelitian di masa depan di bidang ini.